Gender Diversity, Audit Committee and Efficiency in Nepalese Commercial Banks - Sharma, Kishan; Chand, Pawan; Yadav, Ritu; Jha, Sachindra (Nepalese Journal of Economics, 2025)
The study examines the gender diversity, audit committee and efficiency in Nepalese commercial banks. The dependent variables selected for the study are return on assets and earnings per share. The selected independent variables are board size, gender diversity, independent directors, audit committee size, total assets and bank age. The study is based on secondary data of 11 commercial banks with 110 observations for the study period from 2013/14 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of gender diversity and audit committee characteristics on the efficiency of Nepalese commercial banks. The study showed that board size has a positive effect on return on assets and return on equity. It means that higher the number of directors on the board, higher would be the return on assets and return on equity. Similarly, gender diversity has a negative effect on return on assets and return on equity. It means that increase in proportion female directors on board leads to decrease in return on assets and return on equity. The results of the study also shows that audit committee has a positive effect on return on assets and return on equity. It implies that larger the size of audit committee, higher would be the return on assets and return on equity. However, independent director has a negative effect on return on assets. It indicates that increase in number of independent directors on the board leads to decrease in return on assets. Similarly, total assets have a positive effect on return on equity. It implies that increase in total assets of the bank leads to increase in return on equity.